2005
DOI: 10.1021/bi051333h
|View full text |Cite
|
Sign up to set email alerts
|

ASF1 Binds to a Heterodimer of Histones H3 and H4:  A Two-Step Mechanism for the Assembly of the H3−H4 Heterotetramer on DNA

Abstract: The first step in the formation of the nucleosome is commonly assumed to be the deposition of a histone H3-H4 heterotetramer onto DNA. Antisilencing function 1 (ASF1) is a major histone H3-H4 chaperone that deposits histones H3 and H4 onto DNA. With a goal of understanding the mechanism of deposition of histones H3 and H4 onto DNA, we have determined the stoichiometry of the Asf1-H3-H4 complex. We have established that a single molecule of Asf1 binds to an H3-H4 heterodimer using gel filtration, amino acid, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(126 citation statements)
references
References 56 publications
(102 reference statements)
7
119
0
Order By: Relevance
“…These structures have been very rewarding in that they provide intriguing insights into the mechanism of nucleosome disassembly. In vitro and in vivo evidence that Asf1 binds a heterodimer of H3/H4 (and not, as previously assumed, a (H3-H4) 2 tetramer) [51] [52] [53] were confirmed by x-ray crystallography, and the structural basis for these observations became immediately obvious. Asf1 binds the C-terminal α3-helix of H3, preventing the formation of the (H3-H4) 2 through the four-helix bundle (Figure 4).…”
Section: Chaperone -Histone Interactions and Implications For Nucleosmentioning
confidence: 69%
“…These structures have been very rewarding in that they provide intriguing insights into the mechanism of nucleosome disassembly. In vitro and in vivo evidence that Asf1 binds a heterodimer of H3/H4 (and not, as previously assumed, a (H3-H4) 2 tetramer) [51] [52] [53] were confirmed by x-ray crystallography, and the structural basis for these observations became immediately obvious. Asf1 binds the C-terminal α3-helix of H3, preventing the formation of the (H3-H4) 2 through the four-helix bundle (Figure 4).…”
Section: Chaperone -Histone Interactions and Implications For Nucleosmentioning
confidence: 69%
“…Furthermore, we do not think that the influence of Asf1 on H3 acetylation levels could be because of any potential role for Asf1 in shielding histone H3 from deacetylation following its deposition onto the DNA because the crystal structure of Asf1 bound to H3/H4 (22) indicates that Asf1 must be removed from histones H3/H4 to enable interaction with histones H2A/H2B and the DNA within the nucleosome. Our biophysical and structural analyses have clearly shown that the binding of Asf1 to the histone H3/H4 heterodimer envelops the surface of H3 that would otherwise mediate formation of the H3/H4 heterotetramer (30). Upon deletion of ASF1, this H3-H3 interaction interface of the H3/H4 heterodimer is no longer shielded, and it is likely that the soluble H3/H4 in the cell would associate into H3/H4 heterotetramers prior to chromatin assembly.…”
Section: Asf1 Is Likely To Present the Newly Synthesized Freementioning
confidence: 91%
“…However, expectations for the H3-H4 tetramer split model revived in the past few years, after the discoveries that H3-H4 histones deposit onto chromatin as dimers rather than tetramers [28][29][30], and that the histone chaperone Asf1 blocks H3-H4 tetramer formation [31,32] and even disrupts pre-assembled H3-H4 tetramers to form H3-H4/Asf1 heterotrimers [32]. Although without direct evidence, these studies certainly offered a possibility for the H3-H4 tetramer splitting events.…”
Section: Bing Zhu and Danny Reinberg 437mentioning
confidence: 99%